Pseudo-Thrombotic Microangiopathy (Pseudo-TMA): a rare manifestation of vitamin B12 deficiency in a child - Mohd Arif; Nazish Malik (Pediatric Hematology Oncology Journal, 2025)
Vitamin B12 is vital for physiological functions, and its deficiency is relatively frequent in individuals residing in lower-middle-income countries (LMIC). Vitamin B12 deficiency can manifest with mild or severe symptoms and we report an unusual presentation of Vitamin B12 deficiency in an 11-year-old vegan child. The child presented with pseudo-thrombotic microangiopathy (Pseudo-TMA), marked by hemolytic anemia, thrombocytopenia, and schistocytosis. A thorough history, examination, investigations and peripheral smear review confirmed severe macrocytic anemia with pancytopenia, hypersegmented neutrophils, schistocytes and reticulocytopenia. Management included stabilization with blood transfusion, parenteral vitamin B12, and oral multivitamins. A favorable response highlighted the importance of careful clinical evaluation in correctly diagnosing a rare presentation of a hematologic disorder in a child.